Pengembangan Desain Pembelajaran Berdiferensiasi Berbasis Lingkungan untuk Meningkatkan Hasil Belajar Siswa di SD 175771 Siaro - Emelda Thesalonika; Desi Sijabat; Herlina Tinambunan (Jurnal Tematik, 2025)
This study aims to describe the level of feasibility and effectiveness of developing an environment-based differentiated learning design to improve student learning outcomes. This study was conducted at Siaro Elementary School 175771. The subjects of this study were all 30 fourth-grade students of Siaro Elementary School 175771. The research method is Thiagarajan's 4-D development research. The results of the study show (1) the validity of the language expert is 86.53%, and the instructional design expert is 83.33%. From the validation results of the media expert, a score of 86.53 was obtained with a very good category. The effectiveness of the environment-based differentiated learning design can be seen from the improvement of student teaching outcomes, the lowest score is 25 while the highest score is 54. However, after using the environment-based differentiated learning design, the lowest score is 75 and the highest score is 100. The average score of 30 people is 90.26. In addition to the effectiveness of environmentally based differentiated learning design, it can be seen from the results of the increase in the average value (gain) of children's Pretest and Posttest, environmentally based differentiated learning design can improve children's learning outcomes at SD 175771 Siaro, with an average Pretest value of 41.25. While the average posttest is 90.14. Thus, teachers can implement environmental-based teaching designs even though they have not yet reached the dissemination stage, and for other researchers who want to research and make measurements of student learning outcomes, it is necessary to see how the abilities of these students are, the indicators of which are student needs.